Starting with the Spirit: the T&T Clark introduction to Third Article Theology - Habets, Myk (T&T Clark, 2024)
"This volume introduces the reader to both the methodology of TAT and to some of the many theological insights that have arisen from its utilisation. Further, it provides the tools and techniques to invite and inform the reader to participate themselves in the immensely practical and pastoral exercise of viewing reality from a pneumatological perspective, to catch a vision of the world as infused with the power, presence, and potential of the Spirit, and to lead their lives accordingly"--